Myths and Realities: The Fallacy of Faculty Shortages in the Next Decade - Von Zur-Muehlen, Max (Canadian Journal of Higher Education, 1987)
This study confronts the popular conviction that Canadian universities are likely to suffer serious shortages offaculty in the 1990s. Despite an aging professoriate, faculty replacement demand will increase only gradually. Flexible retirement conditions and faculty renewal incentives have lessened the danger of a large simultaneous retirement, and increased demand due to growth is not likely. On the supply side, doctoral enrolment has increased substantially in recent years. Past cohort analysis and projections of enrolment trends indicate that the supply of doctoral recipients will be adequate at least until 1995. Furthermore, holding patterns for recent doctoral graduates and the coming of age of graduate programs in Canada suggest a flexible supply potential in response to any increased demand. This study concludes that in fact there will be a 2:1 faculty supply/demand surplus until at least 1990 and that such a situation will be maintained well into the 1990s.